PENGARUH KINERJA KEUANGAN (ROA) DAN UKURAN PERUSAHAAN (SIZE) TERHADAP NILAI PERUSAHAAN (PER) PT. INDOFOOD SUKSES MAKMUR TBK PERIODE 2010-2018 - Okta Herawati Simarmata; Miftahuddin Miftahuddin; Tohap Parulian (Universitas Medan Area, 2020)
The purpose of this study was to determine whether the Effect of Financial Performance and Firm Size on Company Value at PT. Indofood Sukses Makmur Tbk. This type of research is causal associative research. Causal associative research is research that aims to analyze the relationship between one variable with another variable or how a variable affects other variables. The population in this study are all financial statements at PT. Indofood Sukses Makmur Tbk listed on the Indonesia Stock Exchange for the period 2010-2018. The sample in this study was taken by the saturated sample method. Based on the results of the t test, ROA has a Significant value of 0.153 0.05 which means that ROA has no significant effect on PER. SIZE has a significant value of 0.046 0.05 which means that company size has a significant influence on PER. Based on the results of the F test, ROA and SIZE have a significant value of 0.049 0.05, which means that simultaneously ROA and SIZE have a significant influence on the PER of PT Indofood Sukses Makmur Tbk. The coefficient of determination (R2) value is 0.316. So it can be concluded that 31,6% PER is influenced by ROA and SIZE and the remaining 68,4% is influenced by other variables not examined in this study.